Study of the egret community of the Ardeidae family on Osi Island, West Seram Regency: Ecotourism Area Development Efforts - Pattirousamal, Stella Regina; Eddy, La; Silahooy, Veince Benjamin (Kalwedo Sains (KASA), 2021)
Osi Island is one of the islands in the West Seram Regency, Maluku Province. The existence of egret species on Osi Island can be pursued as a birdwatching ecotourism object. The data is still scanty, it is necessary to do research in an effort to develop ecotourism in the area. This research was conducted on Osi Island, West Seram Regency, from June to July 2021. The method used was point count, a preliminary study was carried out for 3 days to determine observation points. There are 2 species of egrets in the Ardeidae family on Osi Island, West Seram Regency, Maluku Province, namely Egreta alba with 28 individuals and Egreta garzetta with 47 individuals. The results of the analysis showed different individual densities where E. garzetta was superior because of the greater number of individuals than E. alba. Species diversity is in the low category (0.66). Despite the low number of species and individuals, Osi Island still has the potential to become a birdwatching ecotourism destination.